Hakeem Olajuwon: The Dream - Harvey, Miles (Childrens Press Inc, 1994)
These biographies of today's most famous athletes tell of the athletes' triumphs on the field, but also of their most difficult challenges and their often humble beginnings.
Keywords: Juvenile literature-Biography (Hakeem Olajuwon 1963-)-Basketball players (United States)-Blacks (Nigeria)-Non fiction